2022
DOI: 10.1108/ijccsm-04-2021-0040
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge and innovative practices to cope with impacts of climate change on small-scale farming in Limpopo Province, South Africa

Abstract: Purpose This paper aims to describe the indigenous and innovative practices adopted by the small-scale farmers to cope with the impacts of climate change hazards on subsistence farming. Design/methodology/approach The data were collected through focus group discussions with 72 small-scale farmers from a rural community in Limpopo Province, South Africa. The discussions were analysed through verbatim transcripts and content analysis. Findings The study results show the farmers’ understanding of climate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…These limitations can vary considerably across different communities, cultures, and countries. The following subsections (Sections 2.1.1 and 2.1.2) provide a literature-based overview of how some of these factors impact the translation of IK into action-oriented climate-smart adaptation strategies, and there is considerable potential to achieve this in South Africa [16,17] and other developing countries, worldwide [18][19][20][21].…”
Section: Barriers To Ik Translation Into Actionable Cca Strategiesmentioning
confidence: 99%
“…These limitations can vary considerably across different communities, cultures, and countries. The following subsections (Sections 2.1.1 and 2.1.2) provide a literature-based overview of how some of these factors impact the translation of IK into action-oriented climate-smart adaptation strategies, and there is considerable potential to achieve this in South Africa [16,17] and other developing countries, worldwide [18][19][20][21].…”
Section: Barriers To Ik Translation Into Actionable Cca Strategiesmentioning
confidence: 99%
“…In the agricultural sector, for instance, smallholder farming communities in Limpopo, KwaZulu-Natal, and other provinces in South Africa depend on a combination of IK and skills to improve their crop production and adapt to the adverse effects of climate change and food insecurity (Rankoana, 2022). Local farmers employ IK and adaptation mechanisms in rainfall prediction, preparation of the gardens, change of crops, and planting season to ensure better crop yields (Rankoana, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the agricultural sector, for instance, smallholder farming communities in Limpopo, KwaZulu-Natal, and other provinces in South Africa depend on a combination of IK and skills to improve their crop production and adapt to the adverse effects of climate change and food insecurity (Rankoana, 2022). Local farmers employ IK and adaptation mechanisms in rainfall prediction, preparation of the gardens, change of crops, and planting season to ensure better crop yields (Rankoana, 2022). Earlier research conducted by Mapfumo et al (2016) and Nwokocha (2020) found that indigenous communities in South Africa used their vast IK, along with local biological and geographical indicators of seasonal forecasts, to make major strategic, tactical, and operational decisions regarding crop production and management of food stocks in the face of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this was done to prevent the alarm pheromone from reaching the nest and disrupting the colony. Observations were carried out from October to January, which are summer months (Rankoana, 2022), and observation efforts were the same across sites. Since scout release turnover prevented ants from raids, colonies were prevented from hunger stress by observing them only for one foraging session at a time and allowing them to raid at the next foraging session since they have bimodal foragers, viz.…”
Section: Introductionmentioning
confidence: 99%